Crise e evolução cíclica da economia brasileira entre 1990 e 2007: à luz da Teoria Marxiana - Oliveira, Nilton Marques de (2021)
This paper aims to identify and analyze the cyclical behavior of the Brazilian economy from 1990 to 2007, under the perspective of the Marxian Theory. The cyclical movement of the economy is understood as inherent in the capitalist mode of production. The methodology consists in reviewing the literature based on Ribeiro (1988) and Juglar cycle of economy. Data from Instituto de Pesquisa Econômica Aplicada-IPEA (Institute of Applied Economic Research) are used, which are Current Annual Variation Rates of Gross Domestic Product-GDP, Gross Fixed Capital Formation (GFCF), Aggregate Consumption, Rate of Installed Capacity Utilization, and Interest Rate (Selic-Sistema Especial de Liquidação e de Custódia - Special System of Clearance and Custody). It is concluded that, especially in the years following the crisis of 1998, the Brazilian economic cycle become shorter with briefness of all its phases. Based on this study, it is supposed that the recovery periods did not have the duration and intensity of other periods in the past due to the non-occurrence of the economy reorganization.